FACTORS AFFECTING EFFICACY AND IMMUNOLOGICAL RESPONSE OF PESTE DES PETITS RUMINANTS (PPR ) VACCI NES IN SMALL RUMINANTS - Khan; S. B.; U. Sadique; F. A. Khan; I. Ahmad; Z. U. Rehman; M. A. Khan; M. Idrees; Z. Shah (Journal of Animal and Plant Sciences, 2013)
The efficacy of Peste des petits ruminants virus (PPRV) local vaccines available in Pakistan was evaluated on the basis of the humoral immune response measured by haemagglutination inhibition (HI) and agar gel immunodiffusion (AGID) tests in sheep (n=90) and goats (n=90). The effect of storage temperature on HA activity of vaccine virus was measured by holding the vaccine at -20, 4, 27 and 40°C for 24 hours. The titer of freshly prepared vaccine was 1:16 and remained unchanged for 24 hours in the vaccines stored at - 20 and 4°C. However, drop in titer (1:2 HA) was recorded in the vaccine kept at 40°C for 24 hours. The haemagglutination activity of PPR virus constituted in buffer with pH 6.8 and 7.0 was recorded as highest when assay was performed with chicken and human blood group’O’ erythrocytes (1%). The lowest titer was recorded when vaccine was reconstituted in buffer at pH 8.0. After 14th day post vaccination, there was a gradual increase in the antibody titer till 56th day. Geometric mean titer (GMT) of antibodies against locally manufactured PPRV vaccine was higher (207.9) in comparison with Pestivec (73.3), a vaccine imported from Jordan at 63rd day post vaccination in sheep; the corresponding values in goats were 147.0 and 48.5, respectively. All animals of control group were negative for antibodies by both of the diagnostic tests. It was concluded that the efficacy and immunological response of local vaccine (GMT 207) is better than the imported Pestivec (GMT 73.3)
Keywords: PPRV; Pestivec; AGID; HI; sheep; goats